If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2 = x + -11 Reorder the terms: 2 + 4x = x + -11 Reorder the terms: 2 + 4x = -11 + x Solving 2 + 4x = -11 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + 4x + -1x = -11 + x + -1x Combine like terms: 4x + -1x = 3x 2 + 3x = -11 + x + -1x Combine like terms: x + -1x = 0 2 + 3x = -11 + 0 2 + 3x = -11 Add '-2' to each side of the equation. 2 + -2 + 3x = -11 + -2 Combine like terms: 2 + -2 = 0 0 + 3x = -11 + -2 3x = -11 + -2 Combine like terms: -11 + -2 = -13 3x = -13 Divide each side by '3'. x = -4.333333333 Simplifying x = -4.333333333
| (-3)+5+(-5)+12=x | | x/2+3=1/2 | | 6+(-7)+(-5)-(-2)=x | | 6y=45-3y | | 7+(-1)+12-7=x | | (-11)-(-14)+7=x | | 9+6(2)7n= | | 0.5x-1.4=1.1 | | (-7)-(-2)-9=x | | -6-1=-32y+32 | | 16-(-13)-(-5)=x | | 6(y-4)=5[17-3(2y-13)] | | 4-5+7k=33 | | -9-200x+(0.015)(100)= | | (-16)-6+(-5)=x | | 12+0.4(x-2)=10 | | 6(x+2)+4=-6 | | 52x=104 | | 8y-5=6y+7 | | -33m-14=85 | | 5x+5x+3+8=5x+4+4x | | -r+259=-124 | | -2x^2+12x+3=0 | | 3(3+2r)=5-6(r+2) | | 3(2x-4)=5(x+6) | | 7x-6-4x=4x-3 | | 2.1x+1=7 | | 9x-3x=-26+2 | | 7-7x=29x+21 | | 17X^43=100000 | | 145-13= | | 6x+4-4=20 |